Crescimento do ativo e retorno acionário: evidências do mercado brasileiro - Silva, Suelle Cariele de Souza e (2013)
This research aimed to examine the relationship between the asset growth and stock returns in the Brazilian stock market. Initially, we attempted to investigate whether the asset growth effect exists in the Brazilian stock market, as well as ascertain whether the asset growth effect exists when it adjusts the return to the three-factor model of Fama and French (1993) and the four-factor model of Carhart (1997). Then, we sought to verify whether the asset growth separately influences stock returns after controlling other determinants. Finally, we attempted to verify if the asset growth is a risk factor for the explanation of stock returns. The sample consists of all non-financial companies listed on the Stock Exchange in Sao Paulo between June 1995 and July 2013. All accounting data and market were collected in Economatica. To the study development, we used five measures of asset growth and we opted for the employment of both portfolios as well stock-level analysis. For the analysis of the existence of the asset growth anomaly, it was found a difference of portfolios returns with low and high asset growth. Thus, it was found that there is asset growth anomaly, since the difference in returns were positive and significant. Then, the portfolios returns were adjusted to the risk, in order to ascertain the permanence of the effect. It was noticed that neither the three-factor model, neither the four-factor model can capture the asset growth anomaly. To verify if the asset growth is a determinant variable of the return, besides the size, book-to-market and momentum variables, we performed Fama and MacBeth (1973) cross-section regressions methodology. The results indicate that the asset growth is a variable that influences negatively the future return of the stocks in the Brazilian stock market. Finally, to test whether the asset growth is a priced risk factor, we used the common two-stage cross-sectional regression methodology. It has been found that, in three of the five proxies used for asset growth, there is evidence that the asset growth factor is a risk factor priced.